Plant rare trees treasures for younger generation - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
PEKAN, 6 December 2021 - In an effort to increase campus greenery and continue the university’s efforts to preserve a more sustainable campus environment, the Office of the Vice-Chancellor (PNC), Universiti Malaysia Pahang (UMP), recently took the initiative to implement the Sustainable Green Campus Initiative Tree Planting Programme in a special rare plants area spanning 5.3 acres located near the UMP Pekan lake.